Terminal Ileitis due to Yersinia Infection: An Underdiagnosed Situation. (27th May 2020) - Triantafillidis, John K.; Thomaidis, Thomas; Papalois, Apostolos
Abstract : Endoscopy is currently the gold standard for the diagnosis of inflammatory bowel disease (IBD). The presence of macroscopic lesions along with the microscopic detection of inflammatory infiltration in the terminal ileum often leads the gastroenterologist to the diagnosis of Crohn's disease (CD). However, some of these cases could be, in fact, an infection caused by Yersinia spp., accompanied or not with CD, which could be easily diagnosed with the identification of serum antibodies against Yersinia outer protein antigens (YOP antigens). Since Yersiniosis is considered to be an uncommon situation, food and water are not usually checked for the possibility of contamination by Yersinia . Therefore, it is reasonable to assume that the true prevalence of Yersinia infection in patients with terminal ileitis is probably underestimated. In this article, we review the most important data regarding the various aspects of Yersinia infection with special focus on its pathophysiology and diagnosis. We recommend testing for serum antibodies against YOP antigens in all patients with an endoscopic and histological image of terminal ileitis in order to identify Yersiniosis in conjunction or not with terminal ileum CD.